2022
DOI: 10.7759/cureus.29717
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Role of Acorus calamus in Developmental and Histopathological Changes in Autism-Induced Wistar Rats

Abstract: IntroductionAutism spectrum disorder (ASD) is a neurodevelopmental disorder, and a tremendous increase in the incidence of autism poses challenges in identifying the different treatment modalities. Since the defined etiology, pathophysiology, and treatment of autism are unavailable, translational research is being done by creating animal models of autism. This study aimed to assess the effects of Acorus calamus on developmental and histopathological changes in autism-induced Wistar rats. Materials and methodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Research has shown that AC exhibits a neuroprotective effect in autism-induced Wistar rats [ 50 ]. In addition, the administration of AC has been found to be beneficial in treating epilepsy [ 51 , 52 ] and preventing the formation of FeCl-induced epileptogenesis by modulating antioxidant enzymes [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that AC exhibits a neuroprotective effect in autism-induced Wistar rats [ 50 ]. In addition, the administration of AC has been found to be beneficial in treating epilepsy [ 51 , 52 ] and preventing the formation of FeCl-induced epileptogenesis by modulating antioxidant enzymes [ 53 ].…”
Section: Introductionmentioning
confidence: 99%